Aerosol particle mixing state, refractory particle number size distributions and emission factors in a polluted urban environment: Case study of Metro Manila, Philippines - Kecorius, Simonas (Animo Repository, 2017)
Ultrafine soot particles (black carbon, BC) in urban environments are related to adverse respiratory and cardiovascular effects, increased cases of asthma and premature deaths. These problems are especially pronounced in developing megacities in South-East Asia, Latin America, and Africa, where unsustainable urbanization ant outdated environmental protection legislation resulted in severe degradation of urban air quality in terms of black carbon emission. Since ultrafine soot particles do often not lead to enhanced PM10 and PM2.5 mass concentration, the risks related to ultrafine particle pollution may therefore be significantly underestimated compared to the contribution of secondary aerosol constituents. To increase the awareness of the potential toxicological relevant problems of ultrafine black carbon particles, we conducted a case study in Metro Manila, the capital of the Philippines. Here, we present a part of the results from a detailed field campaign, called Manila Aerosol Characterization Experiment (MACE, 2015). Measurements took place from May to June 2015 with the focus on the state of mixing of aerosol particles. The results were alarming, showing the abundance of externally mixed refractory particles (soot proxy) at street site with a maximum daily number concentration of approximately 15000 #/cm3. That is up to 10 times higher than in cities of Western countries. We also found that the soot particle mass contributed from 55 to 75% of total street site PM2.5. The retrieved refractory particle number size distribution appeared to be a superposition of 2 ultrafine modes at 20 and 80 nm with a corresponding contribution to the total refractory particle number of 45 and 55%, respectively. The particles in the 20 nm mode were most likely ash from metallic additives in lubricating oil, tiny carbonaceous particles and/or nucleated and oxidized organic polymers, while bigger ones (80 nm) were soot agglomerates. To the best of the authors’ knowledge, no other studies reported such high number concentration of ultrafine refractory particles under ambient conditions. Inverse modeling of emission factors of refractory particle number size distributions revealed that diesel-fed public utility Jeepneys, commonly used for public transportation, are responsible for 94% of total roadside emitted refractory particle mass. The observed results showed that the majority of urban pollution in Metro Manila is dominated by carbonaceous aerosol. This suggests that PM10 or PM2.5 metrics do not fully describe possible health related effects in this kind of urban environments. Extremely high concentrations of ultrafine particles have been and will continue to induce adverse health related effects, because of their potential toxicity. We imply that in megacities, where the major fraction of particulates originates from the transport sector, PM10 or PM2.5 mass concentration should be complemented by legislative measurements of equivalent black carbon mass concentration. © 2017 The Authors